Direct and indirect challenges for water quality from the hydraulic fracturing industry. Issue 11 (1st November 2014) - Long, Sharon C.
Abstract : This article describes proactive water‐quality monitoring approaches that are useful for water utilities and suppliers concerned with the increased use of hydraulic fracturing in the production of domestic oil and gas.